Long-term compromised immune regulation after rituximab induction in blood group incompatible (ABOi) living-donor renal transplantation – 5 year results of a prospective pilot study - Weimer, Rolf; Karakizlis, Hristos; Renner, Fabrice; Dietrich, Hartmut; Daniel, Volker; Süsal, Caner; Schüttler, Christian; Kämper, Daniel; Leicht, Dominik; Wörlen, Michael; Milchsack, Katrin; Renner, Lene; et al. (Frontiers in Immunology, 2025)
BackgroundAn increased risk of severe infectious disease and acute antibody-mediated rejection (AMR) has been described after ABOi renal transplantation. We performed a prospective renal transplant study up to 5 years posttransplant to detect long-term immunological effects of rituximab administration.MethodsMononuclear cell subsets in peripheral blood, regional lymph nodes and protocol biopsies, in-vitro T and B cell responses, serum sCD30 and neopterin were assessed in 85 renal transplant recipients (living donation: n=25 ABOi, n=30 ABO compatible (ABOc); deceased donation (DD): n=30, all ABO compatible), and IgG anti-HLA antibodies by single antigen assay in ABOc and ABOi patients.ResultsAn increased frequency of severe infectious diseases in ABOi recipients (doubled versus ABOc within 2 years, P = 0.042) coincided with profoundly downregulated peripheral blood B cell subsets for at least 2 years, impaired in-vitro B cell responses (T-dependent: 2 years, versus ABOc: P = 0.004) and significantly lower CD4+ and CD8+ T cell counts (versus ABOc; 6 months, P = 0.046 and 3 months, P = 0.011, respectively). In regional lymph nodes, we found a significant downregulation of naive B cells (P = 0.031) and short lived plasma cells (P<0.0005) at the time of transplantation. In protocol graft biopsies, rituximab induced B cell depletion at 3 months (P<0.001), but counter-regulatory enhanced counts of T cells (P = 0.041), macrophages (P = 0.021) and plasma cells (P = 0.033) at 1 year. This immune activation was associated with a temporary rise in neopterin levels (P ≤ 0.024 versus ABOc, day 14 until 1 year), CD4 helper activity (P = 0.019 versus ABOc at 2 years) and NK cell counts (P = 0.034 versus ABOc, 4 years; P ≤ 0.040 versus DD, 3–5 years), a missing impact of rituximab on sCD30 levels and HLA antibody formation, and an increased frequency of biopsy-proven acute rejection (3–12 months, P = 0.003) and AMR (P = 0.008 within 5 years).ConclusionsAn increased frequency of severe infectious diseases in ABOi renal transplant recipients may be explained by rituximab-induced long-term immunological effects on CD4+ and CD8+ T cell counts and the prolonged depletion of B cell subsets together with compromised B cell responses. In protocol graft biopsies, rituximab induced early B cell depletion but counter-regulatory proinflammatory effects coinciding with an increased acute rejection frequency.Registration DetailsClinicalTrials.gov, identifier NCT01136395; EudraCT, identifier No.: 2009-012198-36.